2022
DOI: 10.3390/agriculture12122034
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Quality Evaluation Using Non-Destructive Approaches: A Review

Abstract: Pomegranate (Punica granatum L.) is one of the most healthful and popular fruits in the world. The increasing demand for pomegranate has resulted in it being processed into different food products and food supplements. Researchers over the years have shown interest in exploring non-destructive techniques as alternative approaches for quality assessment of the harvest at the on-farm point to the retail level. The approaches of non-destructive techniques are more efficient, inexpensive, faster and yield more acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Conventional methods relying on the quantification of different quality traits such as dry matter content, oil content, and moisture content have also been reported in the study of quality parameters of fruits and vegetables; however, these methods were found to be undesirable, destructive, time-consuming, and labor-intensive ( Magwaza and Tesfay, 2015 ; Kyriacou and Rouphael, 2018 ). Therefore, the application of non-destructive bio-sensing methods as a promising alternative for evaluating the value of tropical produce has been adopted ( Ndlovu et al., 2022 ; Okere et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional methods relying on the quantification of different quality traits such as dry matter content, oil content, and moisture content have also been reported in the study of quality parameters of fruits and vegetables; however, these methods were found to be undesirable, destructive, time-consuming, and labor-intensive ( Magwaza and Tesfay, 2015 ; Kyriacou and Rouphael, 2018 ). Therefore, the application of non-destructive bio-sensing methods as a promising alternative for evaluating the value of tropical produce has been adopted ( Ndlovu et al., 2022 ; Okere et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The non-invasive, fast, user-friendly, time saving, and pretreatment-free features of near-infrared spectroscopy (NIRS) makes it an adequate technique for measuring milk quality during the milking process [5][6][7][8][9]. NIRS was used to measure and provide qualitative and quantitative information on agricultural products, including rice, wheat, pomegranate, and carrots [10][11][12][13][14]. NIRS has been used in practice to automatically measure rice quality in Japan [13].…”
Section: Introductionmentioning
confidence: 99%